(untitled) (Journal of Applied Membrane Science & Technology, 2023)
It is worth noticing that structure of nanomaterials affects the membrane performance, however, the effect of diameter of multiwalled carbon nanotubes (MWCNTs) has not been discussed in the past. This research aims to investigate the effect of diameter of MWCNTs on the performance of graphene oxide (GO)/ MWCNTs nanocomposite membrane for methyl orange dye removal. MWCNTs with different diameters (12-15 nm, 30-50 nm) with the same length (< 10 µm) are used to synthesize the nanocomposite membrane. The characteristics of the synthesized nanocomposite membrane were determined by surface hydrophilicity, pore size and porosity, zeta potential, and Fourier-transfer infrared (FTIR) spectroscopy. Besides, the membrane performance was evaluated by the water permeability test, dye rejection test, and antifouling test. The result showed that pure MWCNTs (30-50 nm) nanocomposite membrane (M2b) has the best performance among the synthesized membrane. The dye rejection of M2b membrane reached 86.77% and the normalized flux was approximately 0.82. Lower dye rejection (83.37%) and normalized flux (0.76) were attained by M2a membrane with smaller diameter MWCNTs (12-15 nm). This was due to M2b membrane having a smaller pore size (0.032 nm), which helped reduce the tendency of dye to pass through the membrane. Besides, M2b membrane has a more negative surface charge (-10.93 mV) that produces larger repulsion force, resulting in more dye being rejected. In conclusion, the performance of the synthesized nanocomposite membrane particularly antifouling properties can be enhanced with the addition of MWCNTs with larger diameter.